Acceptable and Unacceptable Growth of Industrial Agglomeration in Urban Environment. Baghdad as Case Study. (Journal of Planner and Development, 2017)
Recent empirical studies of agglomeration economies indicate that economic, social and physical policies are the driving forces affecting spatial distribution of urban environment. Industrial agglomeration is influenced by agglomeration growth and spatial concentration and localization and Physical economics has a strong effect on increasing workers in the manufacturing sector. This paper will be focus in the effect of industrial growth spatially on industrial concentration to determine the trend and size of industrial localization. Census data for industrial employment are used in Location Quotient and Employment Multiplier Analysis. The findings indicate that concentration indicators for two types of industries, basic and non-basic industries in Baghdad are divided in four levels. The first, basic industries are concentrated and recorded an increase in concentration and an acceptable growth in employment. The second, basic industries recorded a decrease in concentration and an acceptable growth employment. The third, non-basic industries recorded an increase in concentration and an acceptable growth in employment. The fourth, non-basic industries are non-concentrated and recorded a decrease in concentration and an unacceptable growth in employment